VITAMIN A CONTENT AND HEDONIC TEST OF MODIFIED MODISCO SLURP PUDDING WITH VARIOUS CARROT EXTRACT ADDITIONS: Kandungan Vitamin A dan Tingkat Kesukaan Puding Sedot Modisco Termodifikasi dengan Penambahan Sari Wortel - Videricka, Eryka Maryta; Ningtyias, Farida Wahyu; Rohmawati, Ninna (Universitas Airlangga, 2024)
Background: A Modisco is PMT-P as treatment for malnutrition and severe malnutrition. To increase acceptance and function of nutritional sources, Modisco is done by modifying shape and composition to become Modisco slurp pudding with the addition of carrot juice. Objectives: The purpose of this study was to analyze the content of vitamin A and the results of the favorite test of the modisco suction pudding with the addition of carrot juice variations of 0%, 5%, 10%, and 15%. Methods: The research design applied was true experimental with 12 experimental units. The vitamin A (beta carotene) content of the samples was determined using Atomic Absorption Spectrophotometry (AAS), and the acceptance test used the Hedonic Scale Test on 80 student aged 9-10 years. The Friedman and Wilcoxon Signed Ranks tests were used to examine the acceptance test results. Vitamin A content were determined using the One Way Anova and multiple comparisons Turkey HSD with a 5% (= 0.05) significant level. The proportion of extract carrot on Modisco slurp pudding was 0% (X0), 5%, 10% and 15% (X1, X2, and X3). Results: The results of the study of vitamin A levels through statistical tests using one-way ANOVA showed that there was a significant difference in vitamin A content compared to variation in the addition of carrot extracts in modisco slurp pudding (p value = 0.0001 <0.05). The results of the hedonic test showed a significant difference in aroma and taste, while color and texture did not differ significantly. Conclusions: The addition of carrot juice to modisco slurp pudding increases vitamin A levels and is preferred in terms of aroma and taste. Based on the vitamin A content test, the addition of 5% (X1) of carrot extracts is more preferred and closest to the daily vitamin A needs of toddlers.